An Exploration of Pre-Service Teachers’ Attitudes Toward Including Students with Autism Spectrum Disorder (ASD) in General Education - Houser, Mary A.; Guerriero, Tara S.; O'Brien, Trevor (Journal of the American Academy of Special Education Professionals, 2024)
This study explored pre-service teachers’ attitudes toward including students with ASD in general education. Ten participants from a mid-size teacher preparation program at a northeastern university participated in a focus group inquiry. The exploratory questions used during the focus group were derived from The Attitude Toward Inclusive Education Scale (ATIES) (Wilczenski, 1992). The Braun and Clarke’s (2006) Model of Analysis was used to identify themes. Results indicated pre-service teachers’ attitudes included both benefits and challenges associated with inclusion. Suggestions for improving pre-service teachers’ attitudes toward including students with ASD were provided.